Analysis on asset acquisition using diminishing musyarakah model / Siti Zaharah Mohd Ruslan - Mohd Ruslan, Siti Zaharah (2014)
Asset acquisition is one of the many strategic ways to expand the business. Due to that, a lot of investment companies and financial institutions are competing with each other in offering the best financing products to the customers. In Malaysia, the financial institution has developed dual banking systems which are conventional and Islamic banking system. This situation gives more opportunities to the customer as entrepreneur to choose the best financial product in managing their investment. One of the products that is introduced by Islamic banks is diminishing musyarakah concept. The application of diminishing musyarakah can help Muslims to avoid lending that is based on riba since it is based on syariah principle. The objective of this study is to determine the net present value and the internal rate of return for a proposed diminishing musyarakah model in calculating the investment performance. This study calculate the net present value using MATLAB and calculate the internal rate of return using bisection method and secant method. The forecast profit rate was also calculated by using the geometric Brownian motion. Then, the net present value for the forecast profit rate and the suitable monthly cash flows using internal rate of return was obtained. It is found that the diminishing musyarakah model can be adapted in determining the investment performance for asset acquisition using net present value and the internal rate of return. Thus, this study may encourage the financial institution and Islamic banks to use the proposed diminishing musyarakah model in managing their investment performance.